Analysing the effects for different scenarios on surrounding environment in a high-density city. (April 2020) - Guo, Jian; Sun, Bingxia; Qin, Zhe; Wong, Man Sing; Wong, Siu Wai; Yeung, Chi Wai; Wang, Hao; ABBA, Sawaid; Shen, Geoffrey Qiping
Abstract: With the development of global urbanization, high-density cities faces enormous challenges on land supply. Hong Kong is a megacity with a long-term lack of land and housing supply. To increase the development intensity of built-up areas in Hong Kong, a minor relaxation of plot ratio/building height restrictions for twenty-one sites in the three target study areas of Kai Tak Development Area has been approved by the Town Planning Board in 2015. This study aims at providing scientific evidence on the impact of this relaxation and possible further relaxations using 3D spatial analyses and simulation technologies. After a 3D model of Kai Tak and surrounding areas being generated, effects of increased PR/BH on skyline, visibility, shadow and insolation, air temperature, and wind ventilation were successfully analysed based on five scenarios. Research findings indicated that, except the extreme case of Scenario 5, no significant changes were found in Scenario 2, Scenario 3 and Scenario 4 when compared with the original plan of Scenario 1. As a pilot study focusing in Hong Kong, this research may also serve to provide new methodological and theoretical insights to facilitate rational discussion and debate on changing land development density in other similar hyper-dense cities. Highlights: We measure impacts of minor relaxation of maximum plot ratio/building height restrictions. 3D models of Kai Tak and surrounding areas are established in GIS virtual environment. We simulate changes of visual and microenvironment using 3D spatial analyses under five scenarios. The most recommended scenario and implications are discussed based on the analysis results. The proposed approach can be applied to other cities in the similar context.